Case Study: Application Of Dhikr And Audio Murottal On Changes Hemodynamic Status In Patient With Post-Thoracotomy Pectus Bar - Azzah Dinah Rachmah; Aan Nur'aeni; Etika Emaliyawati (Padjadjaran Acute Care Nursing Journal, 2022)
Hemodynamic instability is a problem that often occurs in postoperative patients in the ICU, one of which is thoracotomy surgery. Signs of hemodynamic instability are an increase in Mean Arterial Pressure (MAP), heart rate and respiratory rate, changes  in  decreased oxygen saturation, increased pain scale and even decreased consciousness. Maintaining hemodynamic stability in post-operative patients can be done by administering pharmacological and non-pharmacological interventions. Nursing care that can be done to maintain the patient's hemodynamic stability includes oxygenation, head position adjustment, stimulation with both verbal and non-verbal communication approaches, gentle massage relaxation and music therapy. Music therapy that can make patients relax and calm, one of which is by dhikr therapy and listening murottal Al-Quran. Purpose: to analyze dhikr therapy and listening murottal Al-Quran on changes in hemodynamic status in postoperative (thoracotomy) patients. Methods: This study used the case study method to explore  the  problem  of  nursing  care.  The  approach  used  is  the  nursing   care  approach which includes: assessment, diagnoses, interventions, implementation and evaluation. Hemodynamic recording is recorded on a flipchart and pain measurement is carried out using the Critical Pain Observational Tool (CPOT) instrument. Results: The results showed that after 3 days of intervention, there was a decrease in heart rate, respiratory rate, pain scale, increase in GCS values and other hemodynamic component values within normal limits. Conclusion: Therapeutic intervention of dhikr and listening murottal Al-Quran can maintain hemodynamic stability in postoperative patients in the ICU.